Research on Fermentation Technology for a Dendrobium officinale Leaf–Sweet Potato Koji Compound Beverage - Zhenlin Zhang; Zhichao Yin; Yanhong Wang; Xingtang Fang; Xi Chen; Chunlei Zhang; Qingqing Xue; Weiwei Cheng; Meihua Hu; Yixuan Zhu; Yin Yao (Journal of Food Quality)
Dendrobium officinale leaf contains various physiologically active substances. However, no previous studies have reported on the use of D. officinale leaf extract in fermented sweet potato beverages. In this study, Dendrobium officinale leaf and sweet potato were used as raw materials to produce a compound fermented beverage flavored with D. officinale leaf. A sweet potato vinegar folk production method was used, and beneficial microorganisms, including Rhizopus, yeast, and lactic acid bacteria, were inoculated into the fermentation. The quantity of D. officinale leaves, concentration of the sweet potato koji, fermentation time, and temperature during the fermentation process were optimized using orthogonal experiments and analysis of variance. The results indicated that a D. officinale leaf extract of 30%, sweet potato koji concentration of 30%, fermentation time of 5 days, and temperature of 30°C were optimal for beverage formation. Under these conditions, the fermentation broth had a mild flavor of D. officinale leaf and a moderately sweet and sour taste, the biofilm was a transparent gelatinous film, and the utilization efficiency of carbohydrates was high. Excellent flavor, color, and stability of the sweet potato beverage were obtained, with a total sugar content of 15.88 mg/mL and a final pH of 2.65.